Morphing a Plasmonic Nanodisk into a Nanotriangle - Schmidt, Franz P. (American Chemical Society, 2014)
[Image: see text] We morph a silver nanodisk into a nanotriangle by producing a series of nanoparticles with electron beam lithography. Using electron energy loss spectroscopy (EELS), we map out the plasmonic eigenmodes and trace the evolution of edge and film modes during morphing. Our results suggest that disk modes, characterized by angular order, can serve as a suitable basis for other nanoparticle geometries and are subject to resonance energy shifts and splittings, as well as to hybridization upon morphing. Similar to the linear combination of atomic orbitals (LCAO) in quantum chemistry, we introduce a linear combination of plasmonic eigenmodes to describe plasmon modes in different geometries, hereby extending the successful hybridization model of plasmonics.